IS THERE A CURSE OF RELOCATION? ANALYSING THE CAUSAL LINK BETWEEN OFFSHORING AND THE INNOVATION PERFORMANCE OF (SMALL) FIRMS. (23rd November 2015) - Mitze, Timo; Kreutzer, Fabian
ABSTRACT: We analyse the empirical link between offshoring activities and different dimensions of innovation performance at the firm‐level. In order to identify causal effects running from offshoring to innovation, we use a quasi‐experimental comparison group approach by means of (conditional) difference‐in‐difference estimations applied to German establishment‐level data for firms that conducted offshoring activities in the period 2007–13. We find that the international relocation of business functions has a negative impact on the firms' propensity to be innovative in terms of product and process innovations as well as product improvements. While for larger firms the reduction in process innovations is most striking, potentially due to a lack of resources, stagnation in expertise and a reduction in intra‐organizational learning‐by‐doing associated with the relocation of some business activities, for small and medium‐sized enterprises we particularly observe a reduction in product innovations after the offshoring activity has taken place. When interpreting this 'pessimistic' picture on the link between offshoring and the innovation performance of firms, the reader should note that our findings for German establishments have to be assessed through the lens of a global economy in economic recession after 2008, which may have intensified the negative impact of offshoring on the firms' innovation performance.